A benchmark study of DFT-computed p-block element Lewis pair formation enthalpies against experimental calorimetric data - Erdmann, Philipp; Sigmund, Lukas M.; Schmitt, Manuel; Hähnel, Theresa; Dittmer, Linus Bjarne; Greb, Lutz (ChemPhysChem, 2024)
The quantification of Lewis acidity is of fundamental and applied importance in chemistry. While the computed fluoride ion affinity (FIA) is the most widely accepted thermodynamic metric, only sparse experimental values exist. Accordingly, a benchmark of methods for computing Lewis pair formation enthalpies, also with a broader set of Lewis bases against experimental data, is missing. Herein, we evaluate different density functionals against a set of 112 experimentally determined Lewis acid/base binding enthalpies and gauge influences such as solvation correction in structure optimization. From that, we can recommend r2SCAN-3c for robust quantification of this omnipresent interaction.